Visual observation of extraction of a Micra leadless pacemaker from a human cadaver. Issue 9 (28th July 2022) - Bonner, Matthew; Hilpisch, Kathryn; Wika, Kent; Mesich, Mary Lauren; Harris, Megan; White, Troy
Abstract: Introduction: In this article we present the extraction of a Micra from a human cadaver implanted 3 years previously with both visual and X‐ray imaging taken during the removal. Methods: A Micra pacemaker was extracted from a human cadaver with endoscopy and fluoroscopy using a Micra delivery tool. Histological analysis was performed on slices from the tissue surrounding the Micra. Results: The fully encapsulated Micra was easily retrieved with a maximum force of 1.9 pounds. Conclusions: Even though the Micra was implanted almost 3 years previously, the snaring and extraction of the Micra was performed relatively easily and with minimal force required.